(untitled) (LEARNing Landscapes, 2010)
This paper discusses the creation of found poetry using the narratives of children. The author proposes that poetic inquiry offers a place of understanding where the words of children speak volumes. Through this process, she explores how one may connect not only with young people, but also with the often forgotten aspects of the self.